Rewardlessness in orchids: how frequent and how rewardless?. (18th April 2020) - Shrestha, M.; Dyer, A. G.; Dorin, A.; Ren, Z.‐X.; Burd, M.
Abstract: About one‐third of orchid species are thought to offer no floral reward and therefore attract pollinators through deception. Statements of this idea are common in the botanical literature, but the empirical basis of the estimate is rarely mentioned. We traced citation pathways for the one‐third estimate in a sample of the literature and found that the paths lead to empirical foundations that are surprisingly narrow. Moreover, recent measurements have detected minute quantities of sugar available to insect visitors in some orchids thought to be rewardless, raising the possibility of a pollination strategy that is largely deceitful but different to absolute rewardlessness. The orchids are a well‐studied group and there is no doubt that rewardlessness is common in the family. However, greater empirical effort is needed to verify rewardlessness in orchids and to explore geographic and environmental variation in the proportion of rewardless species. Abstract : The frequent claim that one‐third of orchid species are rewardless rests on very thin empirical evidence, and new empirical research will be needed to improve our knowledge of macroevolutionary patterns of deceit pollination.